Research, recovery and mental health: challenges and opportunities. Issue 3 (8th August 2016) - Collins, Padraig; Crowe, Sarah
Abstract : Purpose: – The purpose of this paper is to explore the limitations of the current research paradigm in mental health, particularly from a recovery perspective, and to suggest an alternative approach to clinical research which may be more in line with recovery principles. Design/methodology/approach: – The paper will first review the dominant research methodology utilised by the mental health disciplines, discussing some of the limitations of this approach, particularly from a recovery perspective. Existing research methodologies which embody recovery principles will then be outlined, before an alternative, more recovery-oriented, approach to research is discussed. Findings: – The findings from this paper suggest that the current research paradigm utilised by the mental health disciplines may not be producing the most optimal results, and that a more recovery-oriented approach could help add to the value of this research, while also involving service users and their carers in the research process in a more meaningful way. Research limitations/implications: – This paper will explore possibilities for undertaking recovery-informed research, which has implications, not only for researchers, service users and their families, but also for the practice of mental health disciplines more broadly. Originality/value: – This paper will introduce a critique of traditional research methodology in mental health and will present an alternative recovery-oriented approach which could help to overcome some of the limitations of the more traditional approach.